(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this study was to investigate the maximum Von Misses stress values of implants with different diameters in patients with different bone densities depending on the forces that are applied with different angles to the bone around the implant neck and implant surface, by using finite element analysis method. Material and Methods: 3.8 mm and 4.6 mm diameter dental implants of an implant system that had an in vitro laser-microtextured neck design were used in this study. Computational models were generated for implants with different diameters which were placed in the maxillary and mandibular 1st molar teeth using flat and oblique (20° angled) abutments. Vertical and oblique (30° angled) forces of 300 N were applied to all models and the results were evaluated by finite element analysis.Results: The results show that both vertical and oblique forces on the implants and placement of abutments in the flat and oblique position caused tension in the bone around the neck of the implant and the implant surface. When the oblique and vertical loads applied to the bone models were compared, the forces applied in the oblique direction exhibited a significant increase of Von Misses stress values in the cortical bone around the crest module of the implant compared to the other group. In our study, the minimum stress distribution with respect to the direction of the applied forces and placement positions of the abutments was obtained by applying the implant and the force in the same direction (abutment straight, force vertical). However, in the groups with the angled application of the force direction and the angled placement position of the abutments, the maximum Von Misses stress value increased in the bone around the implant neck and implant surface.Conclusion: Placing the implants at the right angle and within bone tissues with adequate cortical bone density around the implant will ensure minimal stress values on both the supporting bone and the implant surface.